Histomorphometric analysis of the variability of the human skeleton: Forensic implications. (July 2020) - Cummaudo, Marco; Raffone, Caterina; Cappella, Annalisa; Márquez-Grant, Nicholas; Cattaneo, Cristina
Highlights: Osteons and Haversian canals were larger in long and irregular bones. Osteons were smaller in the proximal metaphysis compared the rest of the bone. Haversian canals showed a higher uniformity in the different portions of each bone. Abstract: In the last decades, the histomorphometric analysis of bone tissue has been utilized to develop equations for species discrimination of fragmentary bone. Although this technique showed promising results, its main limitation concerns the lack of knowledge on the histomorphometric variability which may exist between different bones of the skeleton. In a previous study, we demonstrated a significant histomorphological variability in different bones of the same individual and even in different sections of the same bone. The present study aimed at investigating the extent of intra-individual variability in bone histomorphometry throughout the human adult skeleton and areas of a single bone. Samples were taken along an entire medieval male adult human skeleton (aged between 26 and 45 years), including long, flat, irregular and sesamoid bones for a total of 49 cross-sections. The histomorphometric analysis revealed that the size of both Haversian systems and Haversian canals were statistically significantly larger in long and irregular bones compared to flat bones. Moreover, osteons were generally bigger in the diaphysis compared to the proximal and distal metaphyses, whereas Haversian canals showed a higher uniformity in the different portions of each bone. The present study has highlighted the importance of conducting similar studies on both human and nonhuman skeletons at different stages of skeletal maturity in order to shed light on the extent of variability in the size of osteons and Haversian canals. This, in fact, represents an important prerequisite to develop reliable histological methods for species discrimination of fragmented bone.